High Prevalence and Diversity of Cephalosporin-Resistant Enterobacteriaceae Including Extraintestinal Pathogenic E. coli CC648 Lineage in Rural and Urban Dogs in Northwest Spain - Fátima Abreu-Salinas; Dafne Díaz-Jiménez; Isidro García-Meniño; Pilar Lumbreras; Ana María López-Beceiro; Luis Eusebio Fidalgo; María Rosario Rodicio; Azucena Mora; Javier Fernández (MDPI AG, 2020)
The aim of this work was to assess the prevalence of extended spectrum-β-lactamase (ESBL)- and carbapenemase-producing Enterobacteriaceae in fecal samples recovered from rural and urban healthy dogs in Northwest Spain (Galicia) to identify potential high-risk clones and to molecularly characterize positive isolates regarding the genes coding for ESBL/pAmpC resistance and virulence. Thirty-five (19.6%) out of 179 dogs were positive for cephalosporin-resistant Enterobacteriaceae, including Escherichiacoli and Klebsiella pneumoniae (39 and three isolates, respectively). All the isolates were multidrug resistant, with high rates of resistance to different drugs, including ciprofloxacin (71.4%). A wide diversity of ESBL/pAmpC enzymes, as well as E. coli phylogroups (A, B1, C, D, E, F and clade I) were found. The eight isolates (20.5%) found to conform to the ExPEC status, belonged to clones O1:H45-clade I-ST770 (CH11-552), O18:H11-A-ST93-CC168 (CH11-neg), O23:H16-B1-ST453-CC86 (CH6-31), and O83:H42-F-ST1485-CC648 (CH231-58), with the latter also complying the uropathogenic (UPEC) status. The three K. pneumoniae recovered produced CTX-M-15 and belonged to the ST307, a clone previously reported in human clinical isolates. Our study highlights the potential role of both rural and urban dogs as a reservoir of high-risk Enterobacteriaceae clones, such as the CC648 of E. coli and antimicrobial resistance traits. Within a One-Health approach, their surveillance should be a priority in the fight against antimicrobial resistance.